(untitled) (Web of Teachers: Inderscience Research, 2026)
This article explores the pragmatic nature of non-categoric statements in discourse. Non-categoric statements are linguistic units that express uncertainty, probability, or subjectivity rather than absolute certainty. The study examines their role in communication, their linguistic markers, and their pragmatic functions in various contexts. Special attention is given to how such statements contribute to politeness strategies, mitigation, and the speaker’s epistemic stance.